HOW DO GLOBALIZATION CHANNELS AFFECT ECONOMIC GROWTH? EVIDENCE FROM NIGERIA - Sa’idu, Bello Malam; Umaru, Aminu; Yusuf, Mohammed Isa (European Scientific Journal, ESJ, 2014)
The short run and long run relationship between channels of globalization and economic growth are examined in Nigeria using multidimensional econometric models. The unit root suggests that some of the variables are stationary while others are not. Moreover, causality test shows mix outcome with few cases of bi-directional causation. Also, co-integration result reveals the existence of long run relationship between the variables of the model with six co-integrating equations. The paper argues that channels of globalization affect economic growth more positively. Consequently, it recommends the pursuance of policy aiming at reducing external reserves, ensuring foreign exchange rate stability among others.